Diversidade genetica e estrutura populacional de Elaeis oleifera por meio de DArTSeq - Pereira, Valquiria Martins (2015)
The objective of this study was to characterize the genetic structure of 19 native populations of Elaeis oleifera (caiaué) and assess the genetic diversity among samples that make up the Active Germplasm Bank (BAG) of Embrapa, through SNP (Single Nucleotide Polymorphism) and PAVs (Presence/Absence Variants) markers. A total of 552 plants maintained by Embrapa was used for DNA extraction using the CTAB protocol. Genotyping was performed on DArTSeq platform. The filtering of the markers was performed based on Call Rate (> 0.90), and MAF (> 0.05). After these analyzes, the number of SNP markers was reduced to 1,667, and after adding the Q-value parameter (> 2) the number of PAVs, was reduced to 3.187. Genetic diversity analyzes were performed to verify the relationship between E. oleifera subsamples with PAVs markers, as well as to characterize the population structure by means of SNPs markers. We verified the existence of moderate genetic diversity among samples/native populations of E. oleifera (0,301) while also observing the existence of inter and intra-population genetic relationship. The subsamples which are more related to each other are (Autazes and Careiro) and the most distant genetically are (BR 174 and Tonantins). The F index, which measures the inbreeding coefficient, was relatively low for all subpopulations (0.073 on average). Conversely, the observed heterozygosity (Ho) was moderate (0.185 on average) which may be indicative that the subpopulations reproduce mainly by crosses between unrelated individuals. The FST index was, however, high (0.315 on average), demonstrating the existence of structuration, or genetic differentiation among the E. oleifera subpopulations. Structure analysis indeed revealed the existence of 02 to 03 major clusters and the AMOVA indicated that only 54% of the molecular variance occurs within populations. Consequently, for ex situ conservation, the collections should include as many sites as possible. These results further support the hypothesis that the Brazilian Amazon should be a secondary center of diversification of species. The existence of moderate genetic variability among and within populations of Elaeis oleifera, points for commercial exploitation of the species. For breeding, different subsamples/subpopulations should be tested in crosses to maximize diversity.